2016
DOI: 10.1523/jneurosci.4134-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Connectional Modularity of Top-Down and Bottom-Up Multimodal Inputs to the Lateral Cortex of the Mouse Inferior Colliculus

Abstract: The lateral cortex of the inferior colliculus receives information from both auditory and somatosensory structures and is thought to play a role in multisensory integration. Previous studies in the rat have shown that this nucleus contains a series of distinct anatomical modules that stain for GAD-67 as well as other neurochemical markers. In the present study, we sought to better characterize these modules in the mouse inferior colliculus and determine whether the connectivity of other neural structures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
103
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 67 publications
17
103
1
Order By: Relevance
“…Adjacent sections throughout the rostrocaudal extent of the LCIC were stained to determine if the histochemical markers were in relative alignment, thus staining the same modular set. One previous experiment in P8 mice showed that GAD and CO modules are aligned (Lesicko et al, ). This study expands on this finding by examining the co‐registry of NADPH‐d with CO and AChE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adjacent sections throughout the rostrocaudal extent of the LCIC were stained to determine if the histochemical markers were in relative alignment, thus staining the same modular set. One previous experiment in P8 mice showed that GAD and CO modules are aligned (Lesicko et al, ). This study expands on this finding by examining the co‐registry of NADPH‐d with CO and AChE.…”
Section: Resultsmentioning
confidence: 99%
“…The inferior colliculus (IC) is typically portrayed as a midbrain relay hub in the ascending auditory system. This depiction, while fitting for its tonotopically‐arranged central nucleus (CNIC), does not aptly describe its surrounding shell nuclei (the lateral cortex of the IC, LCIC, and the dorsal cortex of the IC, DCIC), that receive a rich array of multimodal inputs (Coleman & Clerici, ; Gruters & Groh, ; Lesicko, Hristova, Maigler, & Llano, ). Many of these projections specifically target the LCIC and exhibit highly compartmentalized terminal distributions in a variety of species (Stebbings, Lesicko, & Llano, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the nBIC/ECIC comprises GAD67‐positive neurochemical modules, which are thought to receive axonal terminations predominantly from somatosensory structures (somatosensory cortex and dorsal column nuclei), while the auditory inputs (from the auditory cortex and the ICc) terminate in the extramodular zones (Lesicko et al . ). Furthermore, a recent study identified an excitatory auditory pathway from the ECIC extramodular zones to the SC in the mouse (Lesicko & Llano, ).…”
Section: Discussionmentioning
confidence: 97%